Focus on Olea europaea L. pruning by‐products: extraction techniques, biological activity, and phytochemical profile. (27th August 2021) - Faraone, Immacolata; Russo, Daniela; Bruno, Maria Roberta; Todaro, Luigi; D'Auria, Maurizio; Milella, Luigi
Abstract: The Olea europaea L. tree has played a central role in Mediterranean culture since ancient times. Several studies have highlighted the health‐promoting properties both of its primary products (olives) and its by‐products (leaves, pomace, husk, stone, mill wastes, and wood). In this study, pruning residues from 25‐year‐old olive trees located in a Mediterranean region (Basilicata, Italy) were analyzed. The antioxidant activity of hydro‐alcoholic extracts from wood samples were analyzed through three complementary in vitro assays. The molecular composition of the extracts was thoroughly evaluated using a gas chromatography apparatus coupled with a mass spectrometer (GC–MS). Our study demonstrated that all but three extracts had remarkable antioxidant activity, which was likely due to the meaningful presence of phenolic compounds, mostly derived from lignin. Moreover, the results showed that bark extracts obtained with ultrasound‐assisted extraction (UAE) had the highest antioxidant activity. In this extract, several known compounds with demonstrated antioxidant activity were found, including hexylresorcinol, 1‐methyl‐ N ‐vanillyl‐2‐phenethamine, and allopurinol. This research suggests that woody olive by‐products are a potential natural resource of antioxidants. These compounds could be useful for functional foods and in industry, and could help to solve the problem of pruning residues, increasing their potential economic value. © 2021 The Authors. Biofuels, Bioproducts and Biorefining published by Society of Industrial Chemistry and John Wiley & Sons Ltd.